Aplikasi Perhitungan Dan Transaksi Penjualan Rumah Secara Kredit Pada PT XYZ - Rika Kharlina Ekawati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2019)
At present the need for housing is increasing in the community.This opportunity is quickly taken by housing developers to offer home sales in cash and credit. PT Lintang Vancar Bumi is one of the housing developers who took this opportunity. But in the calculation of sales transactions carried out still manually. The purpose of this final project is to make a Credit Sales Calculation and Transaction Application at PT Lintang Vancar Bumi for this Application made to help companies make calculations and transactions of home sales, especially on credit and processing data for reporting. The methodology used is mapping of PIECES framework with several stages, namely Performance, Information, Economic, Control, Efficiency and Service . This final project produces a calculation application and home sales transaction on credit that has been adjusted according to the needs of the company in order to be able to provide information and process data in a computerized manner.